Feedback Survey of the Effect, Burden, and Cost of the National Endoscopic Quality Assessment Program during the Past 5 Years in Korea - Yu Kyung Cho; Jeong Seop Moon; Dong Su Han; Yong Chan Lee; Yeol Kim; Bo Young Park; Il-Kwun Chung; Jin-Oh Kim; Jong Pil Im; Jae Myung Cha; Hyun Gun Kim; Sang Kil Lee; et al. (Korean Society of Gastrointestinal Endoscopy, 2016)
Background/Aims In Korea, the nationwide gastric cancer screening program recommends biennial screening for individuals aged 40 years or older by way of either an upper gastrointestinal series or endoscopy. The national endoscopic quality assessment (QA) program began recommending endoscopy in medical institutions in 2009. We aimed to assess the effect, burden, and cost of the QA program from the viewpoint of medical institutions. Methods We surveyed the staff of institutional endoscopic units via e-mail. Results Staff members from 67 institutions replied. Most doctors were endoscopic specialists. They responded as to whether the QA program raised awareness for endoscopic quality (93%) or improved endoscopic practice (40%). The percentages of responders who reported improvements in the diagnosis of gastric cancer, the qualifications of endoscopists, the quality of facilities and equipment, endoscopic procedure, and endoscopic reprocessing were 69%, 60%, 66%, 82%, and 75%, respectively. Regarding reprocessing, many staff members reported that they had bought new automated endoscopic preprocessors (3%), used more disinfectants (34%), washed endoscopes longer (28%), reduced the number of endoscopies performed to adhere to reprocessing guidelines (9%), and created their own quality education programs (59%). Many responders said they felt that QA was associated with some degree of burden (48%), especially financial burden caused by purchasing new equipment. Reasonable quality standards (45%) and incentives (38%) were considered important to the success of the QA program. Conclusions Endoscopic quality has improved after 5 years of the mandatory endoscopic QA program.